Comparison of VMAT‐SABR treatment plans with flattening filter (FF) and flattening filter‐free (FFF) beam for localized prostate cancer. (8th November 2015) - Chung, Jin‐Beom; Kim, Jae‐Sung; Eom, Keun‐Yong; Kim, In‐Ah; Kang, Sang‐Won; Lee, Jeong‐Woo; Kim, Jin‐Young; Suh, Tae‐Suk
Abstract : The purpose of this study is to investigate the feasibility of using a flattening filter‐free (FFF) beam with an endorectal balloon for stereotactic ablative body radiotherapy (SABR) of clinically localized prostate cancer. We assessed plans of SABR with volumetric‐modulated arc therapy (VMAT) that used a flattening filter (FF) beam and an FFF beam and compared the verification results of dosimetric quality assurance for all pretreatment plans. A total of 20 patients with prostate cancer were enrolled in the study. SABR plans using VMAT with two full arcs were optimized in the Eclipse treatment planning system. All plans prescribed 42.7 Gy in 7 fractions of 6.1 Gy each. Four SABR plans were computed for each patient: two with FF beams and two with FFF beams of 6 and 10 MV. For all plans, the cumulative dose‐volume histograms (DVHs) for the target volumes and organs at risk (OARs) were recorded and compared. Pretreatment quality assurance (QA) was performed using the I'm RT MatriXX system and radiochromic EBT3 film to verify treatment delivery, and gamma analysis was used to quantify the agreement between calculations and measurements. In addition, total monitor units (MUs) and delivery time were investigated as technical parameters of delivery. All four plans achieved adequate dose conformity to the target volumes and had comparable dosimetric data. The DVHs of all four plans for each patient were very similar. All plans were highly conformal with CI < 1.05 and CN > 0.90, and the doses were homogeneous (HI = 0.08–0.15). Sparing for the bladder and rectum was slightly better with the 10 MV FF and FFF plans than with the 6 MV FF and FFF plans, but the difference was negligible. However, there was no significant difference in sparing for the other OARs. The mean agreement with the 3 % / 3 %   mm criterion was higher than 97% for verifying all plans. For the 2 % / 2 %   mm criterion, the corresponding agreement values were more than 90%, which showed that the plans were acceptable. The mean MUs and delivery time used were 1701 ± 101 and 3.02 ± 0.17 min for 6 MV FF, 1870 ± 116 and 2.01 ± 0.01 min for 6 MV FFF, 1471 ± 86 and 2.68 ± 0.14 min for 10 MV FF, and 1619 ± 101 and 2.00 ± 0.00 min for 10 MV FFF, respectively. In the current study, the dose distributions of the prostate SABR plans using 6 and 10 MV FFF beams were similar to those using 6 and 10 MV FF beams. However, this study confirmed that SABR treatment using an FFF beam had an advantage with respect to delivery time. In addition, all pretreatment plans were verified as acceptable and their results were comparable. Therefore, the results of this study suggest that the use of an FFF beam for prostate SABR is a feasible and efficient technique, if carefully applied. PACS numbers: 87.55.D, 87.55.dk